2008
DOI: 10.1074/jbc.m709065200
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of Ciliary Neurotrophic Factor with Its Soluble Receptor Protects against Neuronal Death and Enhances Neurite Outgrowth

Abstract: Attempts to promote neuronal survival and repair with ciliary neurotrophic factor (CNTF) have met with limited success. The variability of results obtained with CNTF may, in part, reflect the fact that some of the biological actions of the cytokine are mediated by a complex formed between CNTF and its specific receptor, CNTFR␣, which exists in both membrane-bound and soluble forms. In this study, we compared the actions of CNTF alone and CNTF complexed with soluble CNTFR␣ (hereafter termed "Complex") on neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Exogenous CNTF, on the other hand, had a minimal effect on NL corneal nerve regeneration, but greatly increased nerve-ending branching from nerve fibers in wounded DM corneas. Finally, we showed that CNTFRα is required for maintenance of the sub-basal nerve plexus in UW corneas and for nerve regeneration in the healing corneas Soluble forms of CNTFRα have been detected in serum and cerebrospinal fluid (44) and shown to enhance CNTF-mediated protection against neuronal death and neurite outgrowth (45). Soluble CNTFRα can reconstitute a high-affinity-type CNTFR complex (46).…”
Section: Discussionmentioning
confidence: 93%
“…Exogenous CNTF, on the other hand, had a minimal effect on NL corneal nerve regeneration, but greatly increased nerve-ending branching from nerve fibers in wounded DM corneas. Finally, we showed that CNTFRα is required for maintenance of the sub-basal nerve plexus in UW corneas and for nerve regeneration in the healing corneas Soluble forms of CNTFRα have been detected in serum and cerebrospinal fluid (44) and shown to enhance CNTF-mediated protection against neuronal death and neurite outgrowth (45). Soluble CNTFRα can reconstitute a high-affinity-type CNTFR complex (46).…”
Section: Discussionmentioning
confidence: 93%
“…Another study, using the floxed CNTFR mouse line in which the CNTFR gene was conditionally disrupted, has shown that adult CNTF receptor signaling plays an essential role in motor neuron survival (Lee et al 2008). The coadministration of CNTF with soluble CNTFR protects against neuronal death and enhances neurite outgrowth (Ozog et al 2008). The reduction of Cntfr gene expression in Car9 -/-mice could contribute to the morphological phenotype observed in the central nervous system.…”
Section: Discussionmentioning
confidence: 98%
“…The corresponding protein, CNTFR, is a specific receptor for neurocytokine ciliary neurotrophic factor (CNTF). CNTFR and CNTF are involved in neurite growth and protection from neuronal death (Ozog et al 2008). In fact, CNTF is one of the most potent neuroprotective factors for developmental motor neurons in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, our data suggests that CNTF induces process outgrowth from OT magnocellular neurons, but it remains to be determined if the Jak-STAT pathway is involved in CNTF-induced process outgrowth. However, in response to CNTF, others have demonstrated differential effects of the Jak-STAT, PI3-AKT, and MAPK-ERK pathways in mediating cell survival versus process outgrowth (Alonzi, et al, 2001, Ozog, et al, 2008, Sango, et al, 2008). Thus, CNTF may mediate differential neuroprotective responses via different intracellular signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%